2019
DOI: 10.3389/fpsyt.2019.00658
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Autism Spectrum Disorder: An Epidemiological Study in Shanghai, China

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disease that may involve various brain abnormalities. However, there are few large epidemiological studies on the relation between epilepsy and ASD in terms of different genders and ages. This study aimed to evaluate the relation between epilepsy and ASD based on 74,251 Chinese children aged 3–12 years who were recruited from kindergartens and primary schools in China. ASD was diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(58 reference statements)
1
8
0
Order By: Relevance
“…Epilepsy is a neurological disorder that is characterized by spontaneous and reoccurring seizures (Profa & Franceschettia, 2003). The prevalence of epilepsy in the general population was 4.6/1000 in Northern Italy (Giussani et al, 2014) and 2.4/1000 in China (Zhang et al, 2019), and that of epilepsy in individuals with autism ranges from 2.4% to 46% (Amiet et al, 2013;Anukirthiga et al, 2019;Danielsson et al, 2005;Neumeyer et al, 2019), which significantly exceeded that of the general population. Similarly, ASDs are prevalent in children with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is a neurological disorder that is characterized by spontaneous and reoccurring seizures (Profa & Franceschettia, 2003). The prevalence of epilepsy in the general population was 4.6/1000 in Northern Italy (Giussani et al, 2014) and 2.4/1000 in China (Zhang et al, 2019), and that of epilepsy in individuals with autism ranges from 2.4% to 46% (Amiet et al, 2013;Anukirthiga et al, 2019;Danielsson et al, 2005;Neumeyer et al, 2019), which significantly exceeded that of the general population. Similarly, ASDs are prevalent in children with epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence estimates of epilepsy in autistic individuals reported in the literature are varied (Lauritsen et al, 2002; Surén et al, 2012; Viscidi et al, 2014; Vohra et al, 2017; Williams et al, 2008; Zhang et al, 2019). A previous meta-analysis reported that the prevalence of epilepsy was 21.5% in autistic subjects with intellectual disability (ID) versus 8% in autistic subjects without ID based on the studies published from 1963 through 2006 (Amiet et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…About 25% of children with treatment-resistant epilepsy are comorbid with ASD and often present other severe comorbidities, such as sleep disturbances, intellectual disability, or other psychiatric conditions [ 78 ]. Additionally, as mentioned above, epilepsy is one of the most frequent medical comorbidities in people with ASD [ 12 , 13 , 14 , 15 ], and is also found to be more common in those patients with autism-like behaviors as part of phenotypes of genetic syndromes (i.e., Angelman, Rett syndrome, etc.) [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medical comorbidities are also highly prevalent among the ASD population [ 9 , 10 , 11 ]. In particular, epilepsy represents the most frequent co-occurring neurological condition, affecting 5 to 30% of individuals with ASD [ 12 , 13 , 14 , 15 ]. Even in absence of frank seizures, people with ASD seem to present subclinical electrical discharges with abnormalities in EEG patterns [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as mentioned above, epilepsy is one of the main medical comorbidities in people with ASD [12][13][14][15], and has also been found to be more common in those patients with autism-like behaviors as part of phenotypes of genetic syndromes (i.e. Angelman, Rett syndrome, etc.)…”
Section: Mechanisms Of Action: the Role Of Excitatory/inhibitory Systemmentioning
confidence: 97%